MORAL VALUES IN DYSTOPIAN AND UTOPIAN SOCIETIES: A COMPARATIVE ANALYSIS OF RAY BRADBURY AND ERKIN A’ZAM - Khalilova Shohista Muhammadi qizi (American Journals Publishing, 2025)
This study examines moral values in dystopian and utopian societies as depicted in Ray Bradbury’s Fahrenheit 451 and Erkin A’zam’s Chapaklar mamlakati. Through a qualitative textual analysis, the research investigates how social and political structures shape ethical behavior. The analysis demonstrates that dystopian societies constrain moral autonomy, whereas utopian societies guide moral conduct through collective norms. By incorporating direct textual evidence, the paper highlights the nuanced interplay between social order and morality, emphasizing the cultural and political contexts that influence ethical development.
Keywords: Dystopia, Utopia, Moral Values, Social Structures, Ray Bradbury, Erkin A’zam.